Dampak Penggunaan Teknologi Mobile JKN untuk Memudahkan Pelayanan Kesehatan Pasien BPJS pada Pasien Lanjut Usia - Juanta, Palma; Hutagalung, Katerina; Yulina Purba , Ruth Tasya; Halawa, Juni Swanto; Zebua, Natanael Lata Saro Agassi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of information technology has encouraged the transformation of healthcare services through the utilization of digital applications, one of which is Mobile JKN developed by BPJS Kesehatan. This application is designed to facilitate participants of the National Health Insurance (JKN) program in accessing various healthcare services quickly and efficiently. This study aims to determine the impact of Mobile JKN technology on the accessibility of healthcare services for BPJS patients, particularly elderly patients. The research employed a quantitative method with a survey approach. The study population consisted of elderly BPJS Kesehatan participants who used the Mobile JKN application, with a sample of 30 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through univariate analysis and the Chi-Square test at a significance level of 0.05. The results showed that the majority of respondents had a good level of Mobile JKN usage and perceived healthcare services as more accessible. The bivariate analysis revealed a p-value of 0.001 (p < 0.05), indicating a significant relationship between the use of Mobile JKN and the ease of accessing healthcare services among elderly patients. The Mobile JKN application provides benefits such as online queue registration, access to membership information, and greater efficiency in healthcare administrative processes. However, several challenges were identified, including low digital literacy and limited internet access among some elderly users. Based on the findings, it can be concluded that the use of Mobile JKN technology has a positive effect on the accessibility of healthcare services for elderly BPJS patients. Therefore, enhanced socialization, education, and assistance programs are needed to help elderly users maximize the benefits of the Mobile JKN application.